Mental healthcare for asylum-seekers and refugees residing in the United Kingdom: a scoping review of policies, barriers, and enablers - Teresa Pollard (International Journal of Mental Health Systems, 2021)
Abstract Background Since 2011, a large influx of asylum-seekers and refugees has put pressure on the UK’s under-resourced national health services and mental health services. Asylum-seekers and refugees (ASR) may experience traumatic events pre-departure, life-threating circumstances on their journeys, and difficulties integrating into host countries related to immigration policies, social isolation, poor living conditions, and unemployment, all of which can significantly affect their mental health. This topic is increasingly important due to the numbers of people seeking asylum and growing concern for their mental health on resettlement. This study examined UK-wide policies and guidance, healthcare practices, barriers, and enablers of mental healthcare for ASR residing in the UK. Methods We conducted a scoping review using Arksey and O’Malley’s 2005 framework, which included semi-structured interviews with stakeholders from non-governmental organisations, academia, UK National Health Service, and community groups. We synthesised and analysed literature and interview data thematically to examine current barriers and potential enablers of ASR mental health support in the UK. Results We included 39 literature sources, of 1,638 identified, and 10 stakeholder interviews. Sources, most published in 2019 (n = 13), included data from England (n = 13), Scotland (n = 3), Wales (n = 3), and Northern Ireland (n = 2) and covered access to care (n = 16), mental health disorders (n = 7), impacts on health (n = 7), barriers to care (n = 13), policies and plans (n = 4), and clinical recommendations (n = 3). Synthesised themes from literature and interviews included existing barriers (i.e. communication difficulties and lack of funding, resources, and political will) and potential enablers (i.e. proposed provision practices, social needs of ASR, and policy changes). Conclusions There is a gap in the literature regarding UK-wide assessment of access and delivery of mental healthcare for ASR in the UK. Time sensitive and culturally appropriate approaches are needed, with greater funding and resource support from the UK Government. This study provides justification for a call to relax hostile environment policies, and for ASR-specific mental health services and support to be considered within the UK. Further research is needed to assess implementation of guidelines across the UK.